A Web of Disheartenment With Hope on the Horizon: Intimate Partner Violence in Rural and Northern Communities - Faller, Y. Nichole (Journal of interpersonal violence, 2021)
Intimate partner violence (IPV) has become a worldwide epidemic, yet little is known about the experiences of women survivors living in rural and Northern Canadian communities. Existing statistics suggest that women living in rural areas of the Canadian Prairie Provinces and Northwest Territories (NWT) are at a significantly higher risk of experiencing IPV. To better understand the experiences of IPV in these regions, qualitative interviews were conducted with service providers, including the Royal Canadian Mounted Police (RCMP), Victims Services, Shelter Services, counselors, and others (e.g., physicians). In total, 122 participants were interviewed. These interviews were analyzed using a grounded theory approach where the data/results were transformed into a pictorial matrix that documents the struggles that service providers endure. The matrix/results highlight how social issues, such as isolation and poverty, contribute to social oppressions, such as lack of resources, transportation, and/or services. As service providers struggle against these forces, they begin to develop feelings of disheartenment. Yet, they continue to fight because there are opposing forces, such as Emergency Intervention Orders, police transportation, and Victim Services, that demonstrate how societal response is improving the lives and increasing safety in rural and Northern communities. Ultimately, the results suggest that to reduce the incidences of IPV, we must go beyond the violent acts and deal with the social contexts in which IPV resides.